Susceptibility of rabbits to SARS-CoV-2. Issue 1 (1st January 2021) - Mykytyn, Anna Z.; Lamers, Mart M.; Okba, Nisreen M. A.; Breugem, Tim I.; Schipper, Debby; van den Doel, Petra B.; van Run, Peter; van Amerongen, Geert; de Waal, Leon; Koopmans, Marion P. G.; Stittelaar, Koert J.; van den Brand, Judith M. A.; et al.
ABSTRACT: Transmission of severe acute respiratory coronavirus-2 (SARS-CoV-2) between livestock and humans is a potential public health concern. We demonstrate the susceptibility of rabbits to SARS-CoV-2, which excrete infectious virus from the nose and throat upon experimental inoculation. Therefore, investigations on the presence of SARS-CoV-2 in farmed rabbits should be considered.